Kajian Kritis tentang Konsep Batas Pemberian Maupun Suap dalam Islam - Moch. Azis Qoharuddin (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2020)
Giving/rewarding with bribes, two words that have very different connotations, but often these two words become vague and vague in society. Both are often conserved with one meaning, a bribe, an unsightly word, a great calamity. In this country, bribery bribes are considered commonplace. Even in certain affairs, it is considered a necessity, because without bribes it is almost certain that the affair will be complicated and convoluted. Plus corruption has also become a familiar sight. Bribes are also called bribes or slippery money, which in sharing language is called